THE COVID-19 CONTAINMENT IN INDONESIA AND SOFT LAW: A RISK-TO-OBJECTIVE ANALYSIS - Ibnu, Adi (Bank Indonesia, 2024)
This article illustrates how Basel III, a soft law legal framework guiding how regulators supervise financial institutions in order to prevent and mitigate systemic financial crises, especially the requirement regarding the governance of sovereign debt, is being implemented in Indonesia. The analysis was done by scrutinising the relevant authority’s responses and monetary policy during COVID-19. Also, it examines whether the applicable regulations and other related policies align with the grand objectives of the financial sector. This article provides several important takeaways. First, benefiting from the soft traits of Basel III, the oversight authorities (OJK and BI) have tried to enshrine the government’s resilient and prudent financial state through flexibility. Second, instead of taking expansionary legal measures to stimulate the state’s income and limit the state’s expenses, BI and the government have worked together to contain the damage of the pandemic through a quasi-fiscal program (burden-sharing program, BSP). Third, the legislation of Law No. 3/2023 did not make the BI’s objective less risky. It also suggests that more could have been done to prevent the fiscal deficit, especially by the government, through fiscal consolidation (limiting or decreasing the state’s expenses).